Sharing the Burden? : NATO and its Second-Tier Powers - Zyla, Benjamin (Book collections on Project MUSE., 2015)
Since the fall of the Berlin Wall, NATO's middle powers have been pressured into shouldering an increasing share of the costs of the transatlantic alliance. In Sharing the Burden? Benjamin Zyla rejects the claim that countries like Canada have shirked their responsibilities within NATO. Using a range of measures that go beyond troop numbers and defense budgets to include peacekeeping commitments, foreign economic assistance, and contributions to NATO's rapid reaction forces and infrastructure, Zyla argues that, proportionally, Canada's NATO commitments in the 1990s rivaled those of the alliance's major powers. At the same time, he demonstrates that Canadian policy was driven by strong normative principles to assist failed and failing states rather than a desire to ride the coattails of the United States, as is often presumed. An important challenge to realist theories, Sharing the Burden? is a significant contribution to the debate on the nature of alliances in international relations. --Provided by publisher.